Medical imaging and augmented reality : 7th International Conference, MIAR 2016, Bern, Switzerland, August 24-26, 2016, Proceedings /: 7th International Conference, MIAR 2016, Bern, Switzerland, August 24-26, 2016, Proceedings. (2016) - Unknown
No abstract available